Periwayatan Isra’iliyyat menurut perspektif al-Qur’an dan al-Sunnah - Mohd Nazri Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2003)
History witnesses the infiltration of the elements of Isra’iliyyat into the science of Qur’anic exegesis started widely during the period of tabiin (period of the companions of the Prophet), during the period, many of Qur’anic commentators such as Muqatil bin Sulaimen had narratived the Isra’iliyyat in ther Qur’anic commentaries (tafsir). This article is try to explore the rules of Isra’iliyyat narrative. The evidences from the Qur’an, Sunnah and authoritative commentators are consultated in this study. The finding of this study shows the most of Isra’iliyyat are deviated with the Qur’anis principle, the hadith and logic. Therefore, to accept and preferable the opinion is considered the saiter way assuming that it sources are doubted and it opinions are unacceptable